Phenotypic differences between African and white patients with motor neuron disease: a case-control study. Issue 2 (1st August 2000) - Tomik, B; Nicotra, A; Ellis, C M; Murphy, C; Rabe-Hesketh, S; Parton, M; Shaw, C E; Leigh, P N
Abstract : There is increasing evidence that race may affect the phenotype in some neurodegenerative diseases. To investigate this in motor neuron disease a retrospective case-control study has been carried out on 15 negroid African and 45 white patients with the disease seen over 8 years. Each African was compared with three age and sex matched white patients with motor neuron disease. There were no statistically significant differences in age of onset or the mean duration of disease in the two groups. The chance of presenting with the "flail arm" variant of motor neuron disease was four times as high in the African group than the white group (odds ratio 4.33, p=0.05, 95% confidence interval 0.99–18.92). Although no overall differences in survival were seen between the two groups, in those with the flail arm variant, four out of the six African patients had died whereas all six white arm patients were alive at the censoring date of 1 January 1999 (median follow up 38.5 months). It is concluded that race may influence the phenotype and progression of motor neuron disease.